Persona y realización efectiva de derechos (2013)
This article, doctoral research breakthrough, analyzes the problem of the effectiverealization of rights, particularly with regards to the actual recognition and awardingthereof in their respective subjects, by court orders. This aspect represents a relevantproblem in philosophy and legal theory of our time, specifically in the effectiveprotection of human rights.